TOTAL FLAVONOID DETERMINATION AND ANTIOXIDANT ACTIVITY STUDY OF SPINACH (Amaranthus tricolor L.) RED GITI AND GREEN GITI VARIETY - Any Guntarti; Anita Ruliyani (Jurnal Farmasi Sains dan Praktis, 2020)
Antioxidants in the form of total flavonoids are compounds that can stabilize freeradicals. The mechanism of antioxidants in stabilizing free radicals is give the lackelectron of free radicals and inhibit the formation of free radical formation thatcan damage the body. DPPH method is used to determine the activity of capturingfree radicals of ethanol extracts of Amaranthus tricolor L. red giti and green giti.As a positive control quercetin is used. The results showed that the total amount offlavonoids in red giti spinach was (5.615±0.114)% EK and green giti spinach was(4.468±0.166)% EK. The results also show that all groups have activity as freeradical scavengers. The value of ES 50 for positive control quercetin, red gitispinach extract, and green giti spinach extract are (1.375±0.085)µg/ml,(186.198±0.363)µg/ml, and (209.392± 0.607)µg/ml respectively. Based on ES 50values It can be concluded that antioxidant activity of red giti spinach extract andgreen giti spinach extract are significantly different from the positive controlquercetin. Antioxidant activity of quercetin is categorized strong antioxidantactivity, while the antioxidant activity of red giti spinach extract and green gitispinach extract is categorized as weak antioxidant activity.